2010
DOI: 10.1093/molbev/msq042
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Complexity of Sexual Dimorphism and Sex-Specific Selection

Abstract: Sex-biased gene expression is becoming an increasingly important way to study sexual selection at the molecular genetic level. However, little is known about the timing, persistence, and continuity of gene expression required in the creation of distinct male and female phenotypes, and even less about how sex-specific selection pressures shift over the life cycle. Here, we present a time-series global transcription profile for autosomal genes in male and female chicken, beginning with embryonic development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 53 publications
13
121
1
Order By: Relevance
“…These results are consistent with our previous work in birds that demonstrated that sexbiased gene expression varies greatly through ontogeny and that male-and female-specific selection are ontogenetically decoupled due to sex differences in meiosis and gametogenesis (3). Although male-specific selection acts primarily on male-biased genes expressed in adults once spermatogenesis commences, female-specific selection produces a rapid rate of sequence evolution for genes that are female-biased in late development, with the onset and arrest of oogenesis before hatching (3,13). Our samples are taken from adults in their first reproductive year, as we designed the experiment to examine the power of sexual selection in shaping rates of sequence and expression evolution of male-biased genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with our previous work in birds that demonstrated that sexbiased gene expression varies greatly through ontogeny and that male-and female-specific selection are ontogenetically decoupled due to sex differences in meiosis and gametogenesis (3). Although male-specific selection acts primarily on male-biased genes expressed in adults once spermatogenesis commences, female-specific selection produces a rapid rate of sequence evolution for genes that are female-biased in late development, with the onset and arrest of oogenesis before hatching (3,13). Our samples are taken from adults in their first reproductive year, as we designed the experiment to examine the power of sexual selection in shaping rates of sequence and expression evolution of male-biased genes.…”
Section: Resultsmentioning
confidence: 99%
“…Reads were mapped to these de novo assemblies to obtain sequence, expression, and polymorphism data for one-to-one orthologs between each species and the chicken genome and for one-to-one orthologs shared across the six species. Comparisons of normalized expression counts were used to identify sex-biased gene expression using standard measures and corrected for multiple testing (3,9,47). Ancestral state reconstruction was performed to predict sex bias in the most recent common ancestors from the sexbiased genes found in each of the six species.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, it suggests that male-biased genes accumulate on sex chromosomes, even in homologous regions that still recombine between the Z and the W. In particular, whereas a lack of dosage compensation should be detectable at any developmental stage, sex-biased expression of genes (other than the sex determination genes) should be more pronounced in older embryos, after the full development of gonads (30). Consistent with more sex-specific or sexually antagonistic selection operating at later stages in development, the variance in F/M expression among autosomal genes increased from day 15-42 (P value < 2.2e−16, F test), as did the fraction of sex-biased genes (7-11% using a twofold cutoff; Tables S5-S8).…”
Section: Resultsmentioning
confidence: 99%
“…In evolutionary terms, these miRNAs are probably best viewed as sex-biased, as their expression pattern likely causes them to have a higher impact on fitness in one of the sexes. However, from a regulatory perspective, ovary-biased and testis-biased miRNAs may be better described as tissue-biased, since male and female gonads start diverging from a common tissue precursor in early development and have highly distinct transcriptional programs in adulthood (Mank et al 2010;Necsulea et al 2014). To study the regulatory origins of gonadal miRNA expression, a more detailed investigation of sex-biased miRNA expression throughout development would be a useful first step (Bannister et al 2009).…”
Section: Discussionmentioning
confidence: 99%